The Role of Dance Arts Extracurricular Activities as a Means of Forming Multicultural Attitudes in Students of SMKN 2 Mataram - Fidiatun Fidiatun; Fiqri’ah Fiqri’ah; Ferlina Jayanti; Elda Wati; Elsa Mayora; Sawaludin Sawaludin (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study aims to determine the role of dance extracurricular activities as a means of developing multicultural attitudes in students. Dance activities are viewed as a learning space that not only develops artistic skills but also instills values of diversity through interaction, collaboration, and appreciation for different cultures. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that dance extracurricular activities can be an effective medium for developing multicultural attitudes in students, such as tolerance, mutual respect, and openness to cultural differences. Dance practice activities involving various dances from different regions familiarize students with viewing diversity as a positive thing. Furthermore, the process of working together in groups strengthens a sense of togetherness and empathy among students. Thus, dance extracurricular activities play a vital role in supporting the development of multicultural character needed in both the school environment and society.